2020
DOI: 10.1111/jpm.12610
|View full text |Cite
|
Sign up to set email alerts
|

How are depression and suicidal ideation associated with multiple health risk behaviours among adolescents? A secondary data analysis using the 2016 Korea Youth Risk Behavior Web‐based Survey

Abstract: Accessible summary What is known on the subject? Adolescents who partake in one health risk behaviour (HRB) easily adopt other HRBs, simultaneously or subsequently. Multiple HRBs might threaten adolescents’ future health in adulthood. Adolescents with psychological problems have higher rates of smoking, alcohol use, early sexual initiation and activity, and illicit substance use compared with others. What does this paper add to existing knowledge? A considerable number of Korean adolescents with mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
(106 reference statements)
1
5
0
Order By: Relevance
“…The prevalence estimates of adolescent suicidal behaviors differ considerably depending on the study sampling frame (school‐based vs. household‐based; Gould et al, 2003). The 12‐month prevalence of suicidal ideation, which was identified by use of the household‐based nationwide sample of adolescents in this study, is lower than that reported in studies using a school‐based nationwide sample of South Korean adolescents (12.1%–23.4%) (Kang et al, 2015; Kim, 2014; Kim et al, 2020). In addition, the prevalence rate in this study was lower than in the pooled 12‐month prevalence of suicidal ideation (14.0%) in 82 countries analyzed in the World School‐based Student Health Survey (Biswas et al, 2020).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The prevalence estimates of adolescent suicidal behaviors differ considerably depending on the study sampling frame (school‐based vs. household‐based; Gould et al, 2003). The 12‐month prevalence of suicidal ideation, which was identified by use of the household‐based nationwide sample of adolescents in this study, is lower than that reported in studies using a school‐based nationwide sample of South Korean adolescents (12.1%–23.4%) (Kang et al, 2015; Kim, 2014; Kim et al, 2020). In addition, the prevalence rate in this study was lower than in the pooled 12‐month prevalence of suicidal ideation (14.0%) in 82 countries analyzed in the World School‐based Student Health Survey (Biswas et al, 2020).…”
Section: Resultssupporting
confidence: 87%
“…Female gender and older age are known risk factors for suicidal ideation (Choi et al, 2015; Nam, 2013; Sohn, 2014). The most‐studied personal factors in previous studies were depression, anxiety, hostility, impulsivity, low self‐esteem, smoking cigarettes, and alcohol use (Choi et al, 2015; Hong et al, 2016; Kang et al, 2015; Kim et al, 2020; Kim & Jeon, 2012; Kim & Kim, 2013; Nam, 2013; Oh et al, 2016; Sohn, 2014). Major family‐related factors have included family economic status, family discord, child maltreatment, parent‐child communication, and parent support.…”
Section: Introductionmentioning
confidence: 99%
“…According to a review 13 , 27 , 28 of factors related to depressive symptoms and suicidal ideation in adolescents, we considered sex, school grade, self-rated academic performance, cohabitation with family, subjective health status, smartphone dependency, current alcohol consumption, and current smoking as covariates. Self-rated academic performance was measured through responses to the question: “During the past year, how was your academic performance?” The response options were high, mid-high, middle, mid-low, and low.…”
Section: Methodsmentioning
confidence: 99%
“…Unhealthy behaviors are not only associated with poor healthy conditions of future life for adolescents, but also related to mental health problems that cannot be ignored for the healthy development of young people. For example, both cigarette smoking and alcohol drinking are associated with affective temperament and psychiatric distress, including anxiety and depression, and some suicidal ideation in adolescents ( 8 , 12 , 13 ). In a previous study, it was reported that affective temperament types were independently associated with lifetime suicide attempts ( 14 ).…”
Section: Introductionmentioning
confidence: 99%